The Legality of Rooftop Solar Power Generators Utilization to Fulfill Energy Need: Legalitas Pemanfaatan Pembangkit Listrik Tenaga Surya Atap untuk Memenuhi Kebutuhan Energi - Hediati, Febri Noor; Azim, Saiful (Universitas Muhammadiyah Sidoarjo, 2024)
This legal writing examines the utilization of new and renewable energy as an environmentally friendly approach to electricity consumption. New and renewable energy (EBT) encompasses various primary sources such as solar (PLTS), geothermal (PLTP), water (PLTA), wind (PLTB), etc. To meet the high demand for electricity, harnessing energy from sunlight is explored as an alternative power generator. Utilizing buildings’ roofs for solar cell installation is a common practice. However, challenges arise including the initially high investment for purchasing solar cell components, batteries for energy storage, inverters, and installation costs. Despite these challenges, the monthly operational costs are minimal. The government, through Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 26 of 2021 concerning rooftop solar power systems, supports the legal framework of this which is linked to the electricity grid held by the license holders for electricity supply for public purposes. Furthermore, rooftop solar power systems can be on-grid with the national electricity network (jaringan PLN) to meet energy needs when the installed capacity is below the electricity demand of the consumers. This writing employs a research method with a normative juridical approach by examining literature through a doctrinal perspective. The research results focus on the legality, requirements, and processes involved in the construction of rooftop solar power plants, detailing considerations across various factors before deciding to establish them, including the procedures, regulations, and agreements when integrating rooftop solar power systems into the national electricity network managed by the state electricity company. Highlights: High Initial Investment: Discusses the challenges related to the upfront costs of purchasing solar components, batteries, inverters, and installation despite minimal operational costs. Government Support: Emphasizes the role of government regulations, such as Regulation Number 26 of 2021, in supporting and providing a legal framework for rooftop solar power systems connected to the national electricity grid. Integration with National Grid: Highlights the on-grid capability of rooftop solar power systems, enabling them to supplement energy needs and aligning with the capacity of the national electricity network managed by the state electricity company (PLN). Keywords: Legality, Solar Cell, New and Renewable Energy (EBT), On-Grid.